Smells make the man : a study on the olfactive constitution of masculine beings. - Tan, Jacqueline Wei Hui. (2013)
This study explores the olfactive constitution of masculine beings. It attempts to answer these overarching questions: i) How does one olfactively “qualify” as a “masculine” being? ii) As a scented body, how does one embody being “masculine” in specific fields and iii) how do such olfactively “masculine” practices sustain the larger gender order? By arguing that scenting is a process of performativity that constitutes an “ideal” being within existing discourse surrounding masculinity, this study illustrates how scenting practices and olfactive masculinities are constructed and reconstructed in field-specific power and gender relations so much so that the “masculine” body is lived and experienced in specific contexts. As a scented body, the “masculine” body can therefore have no ontological status apart from the acts of scenting that constitute its reality within field-specific valuations and evaluations of olfactive masculinity.